An Effective Three-Echelon Reverse Supply Chain Strategic Alliance under Cap-and-Trade Regulation - Lin, X. B.; Yu, J. C. P. (ExcelingTech, 2025)
In recent years, the booming industry has led to the extensive development of petrochemical energy, coupled with extensive deforestation, resulting in more serious global warming. Climatic anomalies around the world have made it an imperative for enterprises to effectively limit carbon emissions to protect the environment.In the study, we incorporate carbon emission reduction with implementing corporate social responsibility into a three-echelon reverse supply chain for used products. Assumed that carbon emission depends on sustainability level and the returns (used products) quality is stochastic. The optimization recycling models for both decentralized and centralized systems are formulated and then compared to each other. The results show that the centralized system can achieve higher profits and has lower carbon emissions.This study contributes by: (i) developing closed-loop supply chain models with recycler-manufacturerretailer interactions for reused products; (ii) incorporating both cap-and-trade regulation and green technology investment as emission-reduction mechanisms; (iii) modeling demand as dependent on price and technology level under decentralized and centralized structures; and (iv) providing comparative insights on profits, emissions, and sensitivity, with directions for multi-agent extensions.A computing software Maple 18 has been developed for this purpose and is implemented to derive the optimum decision for for each player. Numerical examples and sensitivity analyses are given to illustrate the results.